Analyze Analyze of User Satisfaction of JKN Mobile Application Service Using Servqual Method in the BPJS Health Area of Surakarta: Analyze of User Satisfaction of JKN Mobile Application Service Using Servqual Method in the BPJS Health Area of Surakarta - Ananda Kurnia Lestari; Aries Widiyoko; Sri Suparti (Journal Health Information Management Indonesian, 2025)
Technological advances in the health sector, such as the Mobile JKN application which was officially launched by BPJS Kesehatan on December 18, 2017 to facilitate access to Health services. The Mobile JKN application is still experiencing technical problems such as login problems, server overload, and data integration. The satisfaction level of users in the BPJS Kesehatan Surakarta area reached 89.71%, there were 10.29% who were dissatisfied, especially regarding the reliability and responsiveness of the application. Negative reviews of online registration and feature incompleteness reflect gaps in services that need to be fixed. This study was a quantitative analytical study with a cross sectional design involving 392 respondents. The data were analyzed using a chi-square test with a significant value of >0.05. Bivariate analysis with the chi square test results in a significant value of less than 0.05, meaning that five dimensions of service quality (reliability (0.025), assurance (0.05), tangibles (0.000), empathy (0.013), and responsiveness (0.004) have a significant relationship with the satisfaction level of the users of the Mobile JKN application. The quality of servqual proved to have a significant relationship with the satisfaction level of JKN Mobile Application users.